Relationship Between Academic Stress Levels And Menstrual Cycle Regularity Among Female Students At Vocational High School Al Azhar - Silviatul Amalia; Sri Aningsih (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
Adolescent girls’ reproductive health can be reflected through the regularity of their menstrual cycles, which are influenced by biological and psychological factors such as academic stress. Stress can disrupt the regulation of reproductive hormones through the activation of the hypothalamic pituitary adrenal (HPA) axis, potentially leading to menstrual irregularities. This study aimed to determine the relationship between academic stress levels and menstrual cycle regularity among adolescent girls at Vocational High School Al Azhar. This study used a cross-sectional methodology and a quantitative analytic observational design. 200 female students in grades X–XII who were chosen using complete sampling made up the study population. A validated menstrual cycle questionnaire and the Perceived Stress Scale (PSS) were used to gather data. The Chi-Square (χ²) test was used to analyze the data. The results showed that most respondents were 17 years old (64.5%) and had normal nutritional status (68.5%). The majority experienced mild stress (59%) and had normal menstrual cycles (85.5%). However, statistical analysis revealed a significant relationship between academic stress levels and menstrual cycle regularity (p = 0.005). The higher the academic stress level, the greater the likelihood of experiencing menstrual irregularities. Therefore, school-based promotive and preventive interventions such as stress management education, healthy sleep patterns, and balanced lifestyle programs are recommended to support adolescent reproductive health